Phytotherapy used for weight loss marketed in pharmacies - Sousa, Deyse Maiane Dias de (2019)
The objective of this article was to identify the phytotherapics used for weight loss marketed in pharmacies. A descriptive, field-based, quantitative approach was conducted with a focus on data collection through portfolios of pharmacies that market herbal medicines for weight loss. Two manipulation pharmacies that market herbal medicines, among them those used for weight loss, were part of the scope of the research. After analyzing the results, a list of 17 herbal products marketed in a municipality in the state of Maranhão was obtained. According to the results of the research, it was observed that the municipality presents a significant variety of herbal medicines marketed that bring, within all their therapeutic actions, benefits for the individuals who are in search of weight loss, encompassing several forms of action in the body. Among the phytotherapics marketed for weight loss, it was identified that the most used pharmaceutical form is in capsules. They act on lipid metabolism, helping to combat weight loss and carbohydrate metabolism.